Evaluasi SMART SOTO Dalam Meningkatkan Kualitas Layanan Kepolisian Kepada Masyarakat Kabupaten Lamongann - Fadhilah, Aisyah; Roekminiati, Sri; Pramudiana, Ika Devy; Sunarya, Aris (Universitas Dr. Soetomo Surabaya, 2023)
The service program policy through the SMART SOTO application is one of the programs initiated by the East Java Regional Police with several Polres ranks, one of which is the Lamongan Police which aims to improve the quality of police services at the Lamongan Police, one of which is the SIM service. The background to the launch of the SMART SOTO Lamongan application was the desire to provide the best service to the community and also to minimize cases of illegal levies during SIM services. The aims of this study were to describe and analyze data: 1) The performance of the SMART SOTO program's policies in improving the quality of police services to the people of Lamongan district and 2) What factors supported and hindered the implementation of the SMART SOTO program in Lamongan District. This study uses evaluation indicators from Willim N. Dunn. This study uses data collection techniques based on interviews, documentation and observation. The results of this study show that the SMART SOTO program, especially SIM services, has demonstrated timeliness, service users, especially young people, are very high, but those aged 30-40 and above are still lacking. In addition, this program is supported by several agencies in Lamongan Regency. The benefits have been felt by the people of Lamongan Regency, this program has been socialized in various crowded places such as the Alun-alun and several sub-districts as well as outreach via Facebook. The SMART SOTO program has shown satisfaction. The SMART SOTO program has become the best choice for the people of Lamongan Regency. Suggestions from researchers should socialization be carried out per village or sub-district so that it reaches more people, the application is only available for the Android version, so it is better if it is upgraded with another version such as iOS, it is necessary to schedule an update for the SMART SOTO application.